Pemaknaan Putusan MA Terkait Calon Legislatif Mantan Koruptor: Analisis Wacana Kritis Sara Mills - Yuri Alfrin Aladdin (Fakultas Ilmu Komunikasi Universitas Pancasila, 2018)
Indonesian Supreme Court of Justice on 14 September 14th, 2018 decided to revoke the law prohibiting ex-corruptor to register themselves as a candidate for legislative members. The decision made such pro-contra among Indonesia people represented on Indonesia medias. One of Indonesia media, Republika (in this research , it was represented by Republika Online/Republika.co.id) as an Islamic media also issued the news articles about the MA’s decision. The media has been recognize to have a special relationship with Islamic political parties in Indonesia and many top rank of the parties have been arrested for corruption cases. In this reserach, I use Critical Discourse Analysis of Sara Mills method and also interview with Chief Editor and a senior journalist of the media to know about the policy of the media. The result of this research, Republika supported the MA’s decision by a number of reasons.